2001
DOI: 10.1111/j.1744-7348.2001.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm communities in conventional wheat monocropping and low‐input wheat‐clover intercropping systems

Abstract: A comparative study was conducted on earthworm communities in a conventional winter wheat monocropping system and a low-input intercropping system in which successive crops of winter wheat were direct-drilled into a permanent white clover sward. Earthworm abundance, biomass and species composition under the two cropping systems in the second and third years of successive cropping were assessed each spring and autumn in farm-scale field plots at four sites using formalin and electrical extraction methods. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 21 publications
7
21
0
2
Order By: Relevance
“…The remaining two soils were taken from a site known as De Bathe (DB) near North Tawton under permanent grazed grassland (G) sown in 1990, typical of the locality, and under a second-year cereal crop arable regime (A). Some further information on this site may be found in Schmidt et al (2001). As a basic soil management regime classification, there were ten arable soils (including fallow and arable-ley treatments) and five grassland soils (including the specific case Broadbalk Wilderness).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The remaining two soils were taken from a site known as De Bathe (DB) near North Tawton under permanent grazed grassland (G) sown in 1990, typical of the locality, and under a second-year cereal crop arable regime (A). Some further information on this site may be found in Schmidt et al (2001). As a basic soil management regime classification, there were ten arable soils (including fallow and arable-ley treatments) and five grassland soils (including the specific case Broadbalk Wilderness).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Clapperton (1999), in Alberta, Canada, showed that on long-term irrigated fields different earthworm species dominated different tillage systems suggesting a preference for different habitats and associations by the different species. In Ireland, Schmidt et al (2001) observed between one and five more earthworm species in a wheat-clover system than in a conventional wheat monocropping system at three out of four study sites; the wheat-clover system with its permanent vegetation cover favoured epigeic and epigeic/anecic ecological groups.…”
Section: Relationship Between Agricultural Practices and Earthworm Pomentioning
confidence: 99%
“…Um dos extratores químicos de minhocas mais utilizados é uma solução de formaldeído (ZABORSKI, 2003), mas a eficiência do método é influenciada pela concentração da solução, temperatura e umidade no solo (RAW, 1959; Lakhani e Satchell citados por ZABORSKI, 2003). Outra desvantagem do método de extração com formaldeído é que esse produto é fitotóxico e carcinogênico e a legislação pode vir a impedir sua utilização (SCHMIDT et al, 2001). …”
Section: Introductionunclassified